Endodontic Management of Maxillary Second Molar with Two Palatal Roots: A Report of Two Cases - Surbhi Patel; Pawan Patel (Case Reports in Dentistry)
Endodontic treatment may sometimes fail because morphological features of the tooth adversely affect the treatment protocol. Maxillary second molars are recognized as usually having a single palatal root with a single palatal canal. The incidence of second palatal root in the maxillary second molar is very rare. Two cases are presented in this paper describing the endodontic management of a four-rooted maxillary second molar with two distinct palatal roots and canals and two distinct buccal roots and canals. Clinical examination and radiographs showed the presence of two palatal roots during the root canal procedure. The canals were biomechanically prepared with crown-down technique and obturated using lateral condensation technique with AH-Plus sealer.